Organizational Culture Factors to Improve Knowledge Sharing Process: A Systematic Literature Review - Hidayat, Ilatifah Nur; Hartanto, Adi; Sensuse, Dana Indra (The Indonesian Journal of Computer Science, 2023)
Knowledge has become a critical aspect and asset of the organization. Thus, to gain benefits from knowledge, organizations must be able to manage that knowledge effectively. One of the processes in knowledge management is knowledge sharing. An important factor in an organization that can influence knowledge sharing is organizational culture. This research was conducted to explore aspects of organizational culture in the knowledge sharing process. This research uses the systematic literature review (SLR) method by Kitchenham to find out what organizational culture can facilitate and hinder the knowledge sharing process. Researchers found 17 journals that were used as sources in compiling a list of organizational cultures that influence knowledge sharing. Based on the research results, it was found that collaboration and top management support aspects are organizational culture factors that can improve the knowledge sharing process. Then, for the knowledge barrier aspect, time constraints were found to be the most frequently discussed factor.